The Quality of Growth : Fiscal Policies for Better Results - López, Ramón E. (Washington, DC: World Bank, 2017)
The world faces unprecedented opportunities to reduce global poverty and improve human welfare. Strong global growth and better economic policies in recent years have substantially reduced poverty in many developing countries. However, with the recent financial turmoil in the United States and rising prices for food, oil, and other commodities, the world economy faces heightened risks and volatility. Policymakers around the world face the challenge of maintaining momentum in growth, as well as of improving the quality of growth. This concern over quality is reflected in the highly uneven reduction in poverty, rising inequality in numerous countries, and widening environmental degradation during the past decade, a period of unprecedented high economic growth in developing countries. Unless these issues are confronted, gains from growth are likely to be undermined and the pace of growth, itself, will not be sustained. Growth is clearly linked to reductions in poverty. But the strength of this relationship depends on the quality or nature of growth. Various studies show that some growth patterns systematically reduce poverty and inequality, but others do not. And some growth patterns lead to underinvestment in human capital, overexploitation of natural resources, and degradation of the environment, patterns inimical to the sustainability of growth.